PERSEPSI AWAL MAHASISWA TERKAIT MATA KULIAH MATEMATIKA: Students' Initial Perception Regarding Mathematics Courses - Aminullah Aminullah; Siti Solihun (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Mathematics is one of the courses that is identical to numbers or calculations, so it is a concern for government science students whose background is social sciences and humanities. The purpose of this study is to describe the perceptions of students of the Government Science Study Program regarding mathematics courses. The research method used in this study is a survey with a quantitative descriptive approach and data analysis using descriptive statistics. The results of the study show that the initial perception of students of the government science study program regarding mathematics courses predominantly states that mathematics is not easy or difficult with a percentage of 49.58%. The initial perception that states it is very not easy or very difficult is 30.83%. While no one has an initial perception that mathematics is very easy. Only 5.42% have the perception that mathematics is easy and 14.17% have the perception that the level of ease of mathematics courses is moderate.